Model Rehabilitasi Berbasis Dayah dalam Reintegrasi Sosial Penyalahguna Narkotika di Kota Lhokseumawe - Thani, Shira; Hidayat, Hidayat; Bahreisy, Budi (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Narcotics abuse in Indonesia, particularly in Lhokseumawe City, continues to rise, while studies on community-based rehabilitation integrating religious values and local wisdom remain limited. Existing approaches are largely dominated by medical models, with insufficient attention to socio-religious dimensions of recovery. This study aims to examine the implementation and effectiveness of a dayah-based rehabilitation model at the Moral and Mental Rehabilitation Center in supporting the social reintegration of former narcotics users. This research employs a qualitative approach, with data collected through observation, in-depth interviews, and document analysis involving stakeholders such as the Islamic Sharia Office, dayah managers, and participants. Data are analyzed through reduction, display, and conclusion drawing. The findings indicate that the center applies a holistic model based on religious teachings and local culture, including spiritual practices, character building, skills development, and social training. This approach is effective in enhancing spiritual awareness and facilitating social acceptance. However, limitations in medical support, assessment procedures, economic empowerment, and aftercare reduce its long-term effectiveness. This study contributes by proposing an integrative rehabilitation framework that connects legal, religious, and social approaches, offering a culturally grounded alternative model while enriching the discourse on rehabilitation and social reintegration.